Museum engagement visits with a universal game-based blended museum learning service for different age groups - Hsu, Tien-Yu; Liang, Hsin-Yi (Library hi tech, 2022)
PurposeThis study develops a universal game-based blended museum learning service (UGBMLS) to engage museum visitors of different ages and promote their return visits. This study aims to provide a single service with flexible learning content matching the diverse needs and preferences for different ages. The contextual influences are considered to promote participatory experiences and meaningful social interactions. An experiment is conducted herein to understand how visitors of different ages experience the museum's services as well as to address the design issues in aiming to satisfy the different age groups' needs.Design/methodology/approachA UGBMLS, which includes a real-world adventure game system with flexible learning content and various types of learning support, was provided for different age groups. To investigate how the visitors of different ages evaluate their experiences with the UGBMLS, a mixed-method study was conducted. In total, two questionnaires were employed to examine the visitors' museum experiences and subjective measurements of cognitive load. In addition, observation and group interviews were used to explain the quantitative results.FindingsThe results show that the UGBMLS can engage diverse visitors of different ages in museum visits and promote their revisit motivations. However, there are significant differences among different age groups. The design issues in seeking to satisfy the diverse needs of different age groups are noted.Practical implicationsThis study provides a feasible and cost-effective approach to support diverse visitors of different ages learning in museums.Originality/valueThis study provides an effective solution for engaging diverse visitors of different ages with a unified service. The results can be used to better understand the needs of different age groups and to effectively improve their museum experiences, thereby boosting their motivation regarding return visits. This study provides a feasible and cost-effective approach to support diverse visitors' learning in museums.